A biomechanical comparison of successful and unsuccessful power clean attempts - Kipp, K.; Meinerz, C. (Sports Biomechanics, 2017)
Although the power clean is an almost ubiquitous exercise in the strength and conditioning setting, relatively little is known about the biomechanics of successful and unsuccessful power clean lift attempts. The purpose of this study was to determine biomechanical differences between successful and unsuccessful power clean lift attempts in male collegiate athletes. Fifteen male lacrosse players (Age: 20.1 ± 1.2; Height: 1.78 ± 0.07 m; Body mass: 80.4 ± 8.1 kg; Relative one-repetition maximum power clean: 1.25 ± 0.13 kg/kg) were videotaped during a lifting session that required the completion of maximal effort power cleans to establish a one-repetition maximum. The position of the barbell was digitised and used to calculate the displacement, velocity, acceleration, and acceleration vector of the barbell. The results revealed that unsuccessful attempts were characterised by differences during the second pull phase. Unsuccessful lifts exhibited greater peak forward barbell displacement, lower backward barbell velocities, and lower resultant acceleration angles during the second pull. Strength and conditioning coaches should therefore emphasise limited forward motion of the barbell during the second pull and instruct athletes to generate a more backward-directed force during the second pull in order to lift greater loads during testing and subsequent lifting sessions. ABSTRACT FROM AUTHOR